Oxytocin infusion dose-response to maintain uterine tone in obese elective cesarean patients: a randomized controlled trial - Yan, Qin-Fang; Ai, Ling; Huang, Yi-Min; Wang, Jianguo; Xiao, Fei; Xu, Huiqin; Tang, Xue-Dong (Frontiers in Pharmacology, 2024)
Background: For cesarean delivery (CD), the 90% effective dosage (ED90) of oxytocin for a first bolus has been established. It is not yet known how much oxytocin to inject into obese women undergoing elective discectomy to keep their uterine tone (UT) appropriate. We hypothesized that patients who are overweight need a greater dose of oxytocin infusion; thus, we aimed to determine how the dose-response curve for oxytocin infusion changes following an initial 1 international unit (IU) bolus in obese women undergoing elective CD.Methods: One hundred parturients with a body mass index (BMI) greater than 30 kg/m 2 were randomly assigned to receive an infusion rate of 14, 18, 22, or 26 IU/h of oxytocin. When the uterine palpation is as hard as touching the forehead or tip of the nose, it is considered sufficient UT according to the criteria used by obstetricians. The median effective dose (ED50) and ED90 values were determined using probit analysis.We found the ED50 and ED90 values for the infusion dose of oxytocin were around 11.0 IU/h and 19.1 IU/h, respectively. Each group had a different number of parturients who needed rescued oxytocin: 14 IU/h for six, 18 IU/h for three, one for 22 IU/h, and none for 26 IU/h. The correlation between the frequency of rescued oxytocin administration and the amount of oxytocin infusion needed to avoid uterine 3 atony was statistically significant (P = 0.02).The present research showed that the most effective dosage of oxytocin infusion for obese parturients undergoing elective CD is 19.1 IU/h, following an initial loading dose of 1 IU. Patients with obesity should receive a greater dosage of prophylactic oxytocin, and further studies comparing patients with and without obesity (with higher BMI) are required.